2016
DOI: 10.17755/esosder.06825
|View full text |Cite
|
Sign up to set email alerts
|

Teog Sinavi T.C İnkilap Tari̇hi̇ Ve Atatürkçülük Dersi̇ Sinav Sorularina İli̇şki̇n Sosyal Bi̇lgi̇ler Öğretmenleri̇ni̇n Algilari

Abstract: ÖzBu araştırmada, Temel Eğitimden Ortaöğretime Geçiş Sınavı (TEOG) ve bu sınavlardaki derslerden biri olan T.C. Đnkılap Tarihi ve Atatürkçülük dersi sınav soruları, sosyal bilgiler öğretmenlerinin görüşlerine göre incelenmiştir. Araştırmada nitel araştırma yöntemlerinden örnek olay yöntemi kullanılmıştır. Araştırmanın çalışma grubunu Adıyaman'da görev yapan 18 sosyal bilgiler öğretmeni oluşturmaktadır. Araştırmanın verileri, yarı yapılandırılmış görüşme yöntemi ile toplanmıştır. Veriler betimsel analiz tekniği… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 1 publication
0
7
0
5
Order By: Relevance
“…The fact that the content and application of the TEOG exams in the context of the scoring system, examination place, exam time, exam type, exam method, result notification, question type, number of questions are consistent with the students [15] as well as corresponding with [1] the school curriculum can be seen as an explanatory factor. TEOG exam questions identified in the study of Erol [5] should be consistent with the activities in the student workbook and the corresponding situation of curriculum and course outcomes can be considered as indicators of these relations which were gained. Similarly, Çelikel and Karakuş [3] found a significant relationship between the success of the TEOG exam and the academic success of the mathematics course.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that the content and application of the TEOG exams in the context of the scoring system, examination place, exam time, exam type, exam method, result notification, question type, number of questions are consistent with the students [15] as well as corresponding with [1] the school curriculum can be seen as an explanatory factor. TEOG exam questions identified in the study of Erol [5] should be consistent with the activities in the student workbook and the corresponding situation of curriculum and course outcomes can be considered as indicators of these relations which were gained. Similarly, Çelikel and Karakuş [3] found a significant relationship between the success of the TEOG exam and the academic success of the mathematics course.…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Yavuz, Odabaş and Özdemir [18], it was found that TEOG mathematics achievement scores were significantly different between the students and between schools and the reason for this difference was that 91% of the students were originated from the students and only 9% were from the schools. As a result of the research conducted by Erol [5], it was found that 64.28% of the social studies teachers participating in the study found the TEOG examination system appropriate. It was concluded that the teachers who participated in the study both agreed about the History of Revolution and the lack of weekly hours of Kemalism course.…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, considering the exams held for admitting students to the secondary education institutions, we can notice that names, content, form, assessment and age groups of the students accepted to the exam have all changed in time. Several exam systems have been experienced under the names of LGS (Transitions to High Schools) in 2000s, OKS (Secondary Education Institutions Exam) from 2004 to 2008, SBS (Placement Test) from 2008 to 2013, and TEOG (Transition from Primary to Secondary Education Exam) from 2013 until now [9], [12], [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible to mention that TEOG is a less stressful exam rather than the previous ones due to having such a property [8]. In a study carried out by Erol [15], it was concluded that TEOG exam was more comprehensive and less stressful in terms of its being coherent with lesson acquisitions and introducing innovations that would decrease exam anxiety and stress. Furthermore, in their research, Öztürk and Aksoy [19] concluded that students expressed positive views upon TEOG exam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation